IMPACT OF NICKEL MEDIATED ARTIFICIAL DIET ON BIOLOGY OF SPODOPTERA LITURA F. (LEPIDOPTERA: NOCTUIDAE) - SHARMILA CHOHAN,; S. C. VERMA,; R. S. CHANDEL,; NEERJA RANA,; MEENA THAKUR, (The Bioscan, 2015)
The pure culture of tobacco caterpillar (Spodoptera litura F.) was maintained under laboratory conditions. Artificial diet impregnated with various concentrations of nickel (T1-0, T2-1, T3-5, T4-10, T5-15, T6-20, T7-30, T8-40 mg Ni/kg) were offered continuously to the larvae for three generations. Each treatment was replicated thrice. Treatment T8 (40 mg Ni/kg) recorded lowest fecundity (472.56 eggs/female) and fertility (73.12%). Significantly lowest fecundity (394.58 eggs/female) and fertility (73.32%) was recorded in generation-3. Minimum incubation period (3.0 days) was recorded with treatment T2 (5 mg Ni/kg) whereas, maximum (4.0 days) was recorded in treatment T7 (40 mg Ni/kg). Minimum incubation period (2.96 days) was recorded in generation -1. Maximum larval period was recorded in Treatment T7 (40 mg Ni/kg) whereas, pupal period was maximum at 1 mg Ni/kg. Longest life cycle was recorded at Treatment T7 (40 mg Ni/kg) 33.64 days. Statistically minimum developmental period 29.76 days was observed in generation-1 as compared to generation -2 and generation-3. Spodoptera litura F. showed dose dependent relationship with the nickel doses in the artificial diet.